2020
DOI: 10.3390/su12208490
|View full text |Cite
|
Sign up to set email alerts
|

A Mixture of Piper Leaves Extracts and Rhizobacteria for Sustainable Plant Growth Promotion and Bio-Control of Blast Pathogen of Organic Bali Rice

Abstract: Rice is a crop that is consumed as a staple food by the majority of the people in the world and therefore failure in rice crops, due to any reason, poses a severe threat of starvation. Rice blast, caused by a fungus Pyricularia oryzae, has been ranked among the most threatening plant diseases of rice and it is found wherever rice is grown. All of the rice blast disease management strategies employed so far have had limited success and rice blast has never been eliminated from rice fields. Hence, there is a nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 48 publications
0
30
0
Order By: Relevance
“…Considering their ability in crop improvement, they are used as a substitute for chemical application in agriculture. Most of the rhizosphere bacteria secrete secondary metabolites called siderophores which act as chelating agents for ferric iron, produced under low iron stress [51][52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…Considering their ability in crop improvement, they are used as a substitute for chemical application in agriculture. Most of the rhizosphere bacteria secrete secondary metabolites called siderophores which act as chelating agents for ferric iron, produced under low iron stress [51][52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…Halophilic Klebsiella sp. isolated from the plant roots showed tolerance to higher levels (4 to 8% NaCl) of salts [ 22 ]. Singh et al, reported the growth of Klebsiella sp.…”
Section: Discussionmentioning
confidence: 99%
“…Various reports claim that the application of PGPR for sustainable improvements in nutrients and the health of soil and plants [ 4 , 9 , 10 , 11 ]. PGPR are known to produce a wide variety of plant growth-promoting traits that include siderophores [ 10 , 11 ], phytohormones [ 12 , 13 ], hydrolytic enzymes [ 14 ], exopolysaccharide [ 15 , 16 , 17 ], stress-tolerant metabolites [ 18 , 19 , 20 , 21 ], and phosphate solubilization [ 22 , 23 ], etc. PGPR through these metabolites promotes seed germination, root and shoot growth, the level of soil and plant nutrients [ 13 , 21 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…This can be met with the help of plant growth-promoting microorganisms (PGPM) [ 7 ] that colonize the rhizosphere and exert beneficial effects on the host plant. PGPM produces phytohormones, hydrolytic enzymes, organic acids, siderophore and biosurfactants to enhance soil fertility, crop yield and combat phytopathogens [ 8 ]. Streptomyces spp.…”
Section: Introductionmentioning
confidence: 99%